What Are the Specific Challenges for SMES in Complying With ESG Reporting? - Győri, Zsuzsanna; Reicher, Regina; Kolnhofer-Derecskei, Anita (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
As a part of a wider research, we proved that Hungarian SMEs (small and medium enterprises) are not just intrinsically motivated to be sustainable and report their sustainable activities and indices but are also compelled to do so by legislation. However, they face limitations such as a lack of resources and knowledge about sustainability. Partly, sustainability should be observed and reported as a part of accounting and corporate reporting. However, sustainability reporting mainly means a form of non-financial reporting that enables companies to communicate their progress in sustainability parameters. Sustainability reporting has only a few compulsory templates and both the EU and national ESG1 regulations are constantly changing, which results in a considerable need for support from entrepreneurs. The first section of this paper provides an extended overview of the various non-financial reporting in historical order. While bigger companies have dedicated departments or employees who are responsible for ESG, the SMEs are looking for help, and require further support, information, training, and advice from outside. This research aims to study experts’ interviews and explore how the experts in regulation, education and consultancy are thinking about the opportunities and challenges for SMEs regarding ESG reporting.